Pengaruh Harga Produk dan Kualitas Pelayanan Bartender Terhadap Kepuasan Tamu di Bar Hotel Mercure Bali - Putri, Komang Shintiya Nita Kristiana; Putra , Anak Agung Anggara; Wijaya, I Gusti Agung Rendra (Universitas Triatma Mulya, 2025)
Mercure Kuta Beach Bali Hotel offers various facilities such as a swimming pool with direct ocean views, a spa, a restaurant, and a bar that provides a relaxing atmosphere for guests. In bartender service, product price and service quality are key to guest satisfaction when visiting the hotel bar. The purpose of this study is to determine the effect of product price and bartender service quality on guest satisfaction at the Mercure Kuta Beach Bali Hotel Bar. This quantitative research analyzes whether there is an influence that makes guests satisfied with visiting the Mercure Bali Hotel Bar. The variables selected in this study consist of two independent variables, Product Price (X1) and Service Quality (X2), and one bound variable, namely Guest Satisfaction (Y). The analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, and F test. The results of the study show that there is an influence between product price and bartender service quality on guest satisfaction. The X1 variable has an effect on Y with a T-calculation value of 3.635> T-table 1.668, as well as the X2 variable has an effect on Y by T-calculation of 2.605> T-table 1.668, while the X1 and X2 variables simultaneously affect Y with a value of 4.641. The product price (X1) with a beta value of 0.331 is more dominant in influencing guest satisfaction (Y) than bartender service quality (X2) with a beta value of 0.095.